Configuration and Transfiguration of Power: Escuela de mandarines by Miguel Espinosa - Lin, Ching-Yu (2014)
The literary thought of Miguel Espinosa revolves around the discourse of Power which discloses the status of Spanish society during Franco´s regimen. Escuela de mandarines, the most representative work of Espinosa, narrates the omnipresence of Power in essay form. This study aims to analyze the configuration and transfiguration of Power from three perspectives. Due to the complexity of the narrative structure, the textual ambition to contain diverse genres and paraphrase details in an encyclopedic way shows an attempt toward universalism, as well as the ironic effect of reductionism. In addition, the language, utilized to describe history, is regarded as a form of fixing accounts through exegesis and manifestation. The total book, full of parodies, outlines an antiutopian world in which the return of repression of Power results in hopelessness.